The storytelling human Lithuanian folk tradition today - Būgienė, Lina, 1968-; Būgienė, Lina, 1968- (Academic Studies Press, 2020)
This book offers significant insights into contemporary Lithuanian folklore research. In a balanced way reflecting upon past and present, tradition and modernity, individual and collective, the eight separate essays comprising the book present a condensed view of the popular Lithuanian culture and mentality.